Three-level Vector Control of Electrically Excited Synchronous Motor for Rolling Mill - NAN Yonghui; ZHANG Chaoyang; ZHENG Hanfeng; GUO Zan; LIN Bo (Kongzhi Yu Xinxi Jishu)
In accordance with the main drive systems of AC-AC and AC-DC-AC rolling mill, an air gap flux oriented vector control strategy was proposed for electrically excited synchronous motor to satisfy three-level AC-DC-AC system, which includes a mixed air gap flux estimator for full speed range, main circuit topology and control of field system and three-level space-vector pulse width modulation strategy. Simulation and test results demonstrate that the control strategy has good dynamic and static performances.